The Way to Peace - JOTIKA, Dr. (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง, 2018)
There are many ways which are used in the world for peace. Some are bad ways and some are good ways for peace. Bad ways is a  term for doing what ought not to be done and not doing what ought to be done, out of zeal (desire), hate, delusion, and fear. They are called 'bad ways' because they are ways not to be travelled by Noble Ones.